'I love my body': Depictions of sex and romance in disability music culture. (March 2018) - Skinner, Anthea
The international disability music scene is a thriving musical subculture consisting of performers self-identifying as disabled who use their performances to explore experiences of living with disability. As a genre predominantly written by, about and for people with disabilities, it provides a space for discourse about life with disability which is largely unmediated by governmental policy, political correctness or able-bodied facilitators. As such, it is a medium through which people with disability are free to express opinions about sex and romance rarely seen in mainstream media. This article examines the ways in which the topics of sexuality and romance are explored within disability music culture. It will focus on four case study songs, I Love My Body (1988) by Johnny Crescendo, Vagina Ain't Handicapped (2011) by Laura Martinez, Def Deaf Girls (2012) by Sean Forbes and No Goodbyes (2012) by Rory Burnside and Rohan Brooks from Rudely Interrupted. These four songs will be used to explore the themes of body image, cultural expectations of the disabled body, the benefits of dating fellow members of the disability community and relationships. This article also draws on the author's own experience as a person with disability and a musician in a band that regularly performs on the disability music scene.